Arendtian Rightlessness and Palestinian Exile in Mourid Barghouti’s I Saw Ramallah - Rusdi, Mohammad Ilham Fahmi; Halimi, Halimi; Basid, Abdul (JOURNAL OF LANGUAGE, 2026)
This study examines the representation of exile and the loss of “the right to have rights” in Mourid Barghouti’s I Saw Ramallah through Hannah Arendt’s political thought. It argues that exile in the memoir is not merely a condition of geographical displacement but a structural form of political exclusion that deprives Palestinian subjects of homeland, legal recognition, mobility, sovereignty, and social belonging. Using a qualitative method with an interpretive-critical approach, this study analyzes selected narrative fragments, spatial symbols, and textual descriptions related to displacement, statelessness, alienation, restricted movement, and collective trauma. The findings show that Barghouti represents exile as a multidimensional violation of human rights. The Palestinian subject is not only alienated from territory but also separated from the political community that should guarantee fundamental rights. The transformation of homeland into occupied space, the ambiguity of citizenship, the status of the “outcast,” and the denial of return reveal a condition of rightlessness. Through Arendt’s framework, the memoir demonstrates that human rights cannot function effectively without political membership and legal recognition. This study concludes that I Saw Ramallah offers a literary critique of political structures that deny Palestinians the fundamental conditions for possessing and claiming rights.